Ramadan and Road Traffic Crashes Nexus: A Multi-Professional Perspective - Yousaf Ali; Ahmed Owais Durrani; Muhammad Sabir (Journal of Road Safety)
Muslims across the world observe fast during the month of Ramadan. Fasting may have positive and negative impacts on the human body, and subsequently, it may have implications for road traffic crashes (RTC). While the existing scholarly literature discusses fasting and the RTC nexus, hardly any study ranks various factors contributing to RTC during Ramadan. This study investigates the RTC and Ramadan nexus while ranking social and health factors associated with Ramadan. The study is based on surveys from Pakistani experts considering the local context. The study also contributes methodologically by using a triangular fuzzy approach incorporated with the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS), a multi-criteria decision-making (MCDM) technique. The analyses suggest lack of sleep, absences of licensing and driver carelessness were three major sources of RTC during Ramadan. Weather had the least effect and neither the number of vehicles nor nutrition were identified as critical factors in road traffic crashes.